IMPLEMENTASI PEMBELAJARAN MAKHARIJUL HURUF DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SANTRIWATI DI PONDOK PESANTREN MASKANUL MUTTAQIN JAMBI - Maulina, Nurul; Sururudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study focuses on the implementation of makharijul huruf learning in improving the Qur’anic reading ability of female students (santriwati) at Maskanul Muttaqin Islamic Boarding School, Jambi, as well as identifying the supporting and inhibiting factors in its implementation. Makharijul huruf learning plays an important role in shaping accurate pronunciation of the Arabic (Hijaiyah) letters in accordance with the rules of tajwid, thereby producing correct and proper Qur’anic recitation. Accurate Qur’anic reading ability is not only related to the technical aspects of pronunciation, but also influences the understanding of meaning and the level of devotion in reciting the Qur’an. Therefore, makharijul huruf learning needs to be implemented in a planned, systematic, and sustainable manner. This research employs a qualitative approach using a descriptive method. The research subjects include the mudir (head of the boarding school), ustadzah (female teachers), and santriwati of Maskanul Muttaqin Islamic Boarding School who are directly involved in the makharijul huruf learning process. Data were collected through observation of the learning process, in-depth interviews with informants, and documentation related to learning activities. Data analysis techniques consisted of data reduction, data presentation, and drawing conclusions to obtain a comprehensive description of the implementation of makharijul huruf learning. Data validity was ensured through source triangulation and technique triangulation. The results of the study are expected to show that the implementation of makharijul huruf learning at Maskanul Muttaqin Islamic Boarding School, Jambi, is carried out in a structured manner through the delivery of theoretical and practical materials on a regular basis, accompanied by direct guidance from teachers. The learning process emphasizes the accuracy of makhraj and the characteristics of letters, as well as repeated Qur’anic reading exercises to improve the students’ reading ability. Supporting factors include a well-organized learning schedule, intensive guidance from educators, and a conducive and religious boarding school environment. Meanwhile, inhibiting factors include differences in students’ educational backgrounds, lack of discipline and independent practice, limited learning time, and facilities and infrastructure that are not yet fully optimal.